Ageism and COVID-19: an integrative review - Manso, Maria Elisa Gonzalez (2021)
This research brings an integrative review on the theme “Ageism during the COVID-19 pandemic”, seeking to answer the question whether there was an outbreak of ageism during the pandemic or simply the visibility of stereotypes already presents in society. The review followed the steps provided by the PRISMA protocol - Key Items for Reporting Systematic Reviews and Meta-analyzes having selected 34 articles from August to October 2020 and from April to June 2021. The resurgence of stereotypes already presents against the age group composed of elderly people is observed, which was treated homogeneously. Portrayed as a burden to society, the elderly was widely associated with decline, uselessness, and dependence mainly by governments, health professionals, the media, and social networks. Such attitudes reinforced intergenerational conflicts, prejudice, and discrimination. However, manifestations of empathy also emerged in contrast to those positions. It is noteworthy that, in a world where social vulnerabilities, access to care and the social determination of falling ill have become especially visible by the pandemic, it is important to firmly confront ageism in all its forms, offering hope for groups in social disadvantage. Finally, we highlight the little interest that the topic aroused in the national academic literature, being much more widely analyzed, and discussed outside Brazil, as observed in this review.